A Randomized, Double-blind, Multicenter Trial Comparing Efficacy and Safety of Imipenem/Cilastatin/Relebactam Versus Piperacillin/Tazobactam in Adults With Hospital-acquired or Ventilator-associated Bacterial Pneumonia (RESTORE-IMI 2 Study). (12th August 2020) - Titov, Ivan; Wunderink, Richard G; Roquilly, Antoine; Rodríguez Gonzalez, Daniel; David-Wang, Aileen; Boucher, Helen W; Kaye, Keith S; Losada, Maria C; Du, Jiejun; Tipping, Robert; Rizk, Matthew L; Patel, Munjal; et al.
Abstract: Background: Imipenem combined with the β-lactamase inhibitor relebactam has broad antibacterial activity, including against carbapenem-resistant gram-negative pathogens. We evaluated efficacy and safety of imipenem/cilastatin/relebactam in treating hospital-acquired/ventilator-associated bacterial pneumonia (HABP/VABP). Methods: This was a randomized, controlled, double-blind phase 3 trial. Adults with HABP/VABP were randomized 1:1 to imipenem/cilastatin/relebactam 500 mg/500 mg/250 mg or piperacillin/tazobactam 4 g/500 mg, intravenously every 6 hours for 7–14 days. The primary endpoint was day 28 all-cause mortality in the modified intent-to-treat (MITT) population (patients who received study therapy, excluding those with only gram-positive cocci at baseline). The key secondary endpoint was clinical response 7–14 days after completing therapy in the MITT population. Results: Of 537 randomized patients (from 113 hospitals in 27 countries), the MITT population comprised 264 imipenem/cilastatin/relebactam and 267 piperacillin/tazobactam patients; 48.6% had ventilated HABP/VABP, 47.5% APACHE II score ≥15, 24.7% moderate/severe renal impairment, 42.9% were ≥65 years old, and 66.1% were in the intensive care unit. The most common baseline pathogens were Klebsiella pneumoniae (25.6%) and Pseudomonas aeruginosa (18.9%). Imipenem/cilastatin/relebactam was noninferior ( P < .001) to piperacillin/tazobactam for both endpoints: day 28 all-cause mortality was 15.9% with imipenem/cilastatin/relebactam and 21.3% with piperacillin/tazobactam (difference, −5.3% [95% confidence interval CI, −11.9% to 1.2%]), and favorable clinical response at early follow-up was 61.0% and 55.8%, respectively (difference, 5.0% [95% CI, −3.2% to 13.2%]). Serious adverse events (AEs) occurred in 26.7% of imipenem/cilastatin/relebactam and 32.0% of piperacillin/tazobactam patients; AEs leading to treatment discontinuation in 5.6% and 8.2%, respectively; and drug-related AEs (none fatal) in 11.7% and 9.7%, respectively. Conclusions: Imipenem/cilastatin/relebactam is an appropriate treatment option for gram-negative HABP/VABP, including in critically ill, high-risk patients. Clinical Trials Registration: NCT02493764. Abstract : Imipenem/cilastatin/relebactam was noninferior to piperacillin/tazobactam for treating hospital-acquired and ventilator-associated bacterial pneumonia (HABP/VABP), with a comparable tolerability profile. Imipenem/cilastatin/relebactam is an efficacious treatment option for nosocomial pneumonia, including HABP/VABP in mechanically ventilated and critically ill, high-risk patients.